ДВА АСПЕКТА ТЕМЫ ДЕТСТВА В РАССКАЗАХ А.П. ЧЕХОВА - Базилевская, Аэлита (Acta Neophilologica, 2008)
There are two main aspects in Chekhov’s stories about children: perception of the world by a child and perception of children’s world by adults. Chekhov shows the moments in the life of children which let to reveal problems that arise because the grown-ups don’t understand the world of child, so children collide with the world of adults, not seldom alien and incomprehensible for them. Children don’t accept insincerity, cruelty, indifference, therefore they are often lonely and defenseless. Thinking about children, Chekhov thought about grown-up problems which became painful for him: about awkward, abnormal life, about mercenary spirit and love of gain that are the bane of people’s life. And at the same time - this is the circle of his thoughts about beauty, created by human and nature, about free and happy people, about possibility of happiness in itself.